Disseminated Tuberculosis in an Immunocompetent State: A Case Report - Singh, Jitendra; Dinkar, Anju; Patel, Nitish K.; Bhavya J; Dewangan, Ankita; Kumar, Nilesh; Kumar, Kalish (Infectious Disorders - Drug Targets, 2023)
Background: Tuberculosis is one of the major infectious diseases of mankind and remains a significant health concern, especially in developing countries. Clinical manifestations of TB are broad and sometimes very challenging for clinicians to diagnose early. Tuberculous psoas abscess was generally secondary to spinal tuberculosis or direct extension from adjacent structures in immunocompromised individuals, but tuberculous psoas abscess in the immunocompetent state is very infrequent. In addition, pancytopenia and new onset neck swelling simultaneously make this presentation a very unusual clinical entity in tuberculosis. Case Presentation: We now present a case of a 21-years-old, unmarried, otherwise healthy girl presented with fever, lower abdominal pain and weight loss for two months. She also noticed painless neck swelling for 15 days. She later had a tuberculous left sided psoas abscess with pancytopenia and a cold abscess on the left side of the neck with no sign of any other apparent focus, according to the evidence. Diagnosis of disseminated TB without lung involvement was established and ATT was started. The outcome was successful on follow up. Conclusion: Among the broad spectrum of atypical manifestations of TB, this case report draws attention to its rarity, diagnostic challenge and awareness of the clinical spectrum, especially in developing countries.
Keywords: psoas abscess